A multiwavelength search for black widow and redback counterparts of candidate γ-ray millisecond pulsars. Issue 4 (17th August 2020) - Braglia, C; Mignani, R P; Belfiore, A; Marelli, M; Israel, G L; Novara, G; De Luca, A; Tiengo, A; Saz Parkinson, P M
ABSTRACT: The wealth of detections of millisecond pulsars (MSPs) in γ-rays by Fermi has spurred searches for these objects among the several unidentified γ-ray sources. Interesting targets are a sub-class of binary MSPs, dubbed 'black widows' (BWs) and 'redbacks' (RBs), which are in orbit with low-mass non-degenerate companions fully or partially ablated by irradiation from the MSP wind. These systems can be easily missed in radio pulsar surveys owing to the eclipse of the radio signal by the intra-binary plasma from the ablated companion star photosphere, making them better targets for multiwavelength observations. We used optical and X-ray data from public data bases to carry out a systematic investigation of all the unidentified γ-ray sources from the Fermi Large Area Telescope Third Source Catalog, which have been pre-selected as likely MSP candidates according to a machine-learning technique analysis. We tested our procedure by recovering known binary BW/RB identifications and searched for new ones, finding two possible candidates. At the same time, we investigated previously proposed BW/RB identifications and we ruled out one of them based upon the updated γ-ray source coordinates.